Selective Heart Irradiation Induces Cardiac Overexpression of the Pro-hypertrophic miR-212 - Sárközy, Márta; Gáspár, Renáta; Zvara, Ágnes; Kiscsatári, Laura; Varga, Zoltán; Kővári, Bence; Kovács, Mónika G.; Szűcs, Gergő; Fábián, Gabriella; Diószegi, Petra; Cserni, Gábor; Puskás, László G.; et al. (Frontiers in Oncology, 2019)
Background: A deleterious, late-onset side effect of thoracic radiotherapy is the development of radiation-induced heart disease (RIHD). It covers a spectrum of cardiac pathology including also heart failure with preserved ejection fraction (HFpEF) characterized by left ventricular hypertrophy (LVH) and diastolic dysfunction. MicroRNA-212 (miR-212) is a crucial regulator of pathologic LVH via FOXO3-mediated pathways in pressure-overload-induced heart failure. We aimed to investigate whether miR-212 and its selected hypertrophy-associated targets play a role in the development of RIHD. Methods: RIHD was induced by selective heart irradiation (50 Gy) in a clinically relevant rat model. 1, 3 and 19 weeks after selective heart irradiation, transthoracic echocardiography was performed to monitor cardiac morphology and function. Cardiomyocyte hypertrophy and fibrosis were assessed by histology at week 19. qRT-PCR was performed to measure the gene expression changes of miR-212 and forkhead box O3 (FOXO3) in all follow-up time points. The cardiac transcript level of other selected hypertrophy-associated targets of miR-212 including extracellular signal-regulated kinase 2 (ERK2), myocyte enhancer factor 2a (MEF2a), AMP-activated protein kinase, (AMPK), heat shock protein 40 (HSP40), sirtuin 1, (SIRT1), calcineurin A-alpha and phosphatase and tensin homolog (PTEN) were also measured at week 19. Cardiac expression of FOXO3 and phospho-FOXO3 were investigated at the protein level by Western blot at week 19. Results: In RIHD, diastolic dysfunction was present at every time point. Septal hypertrophy developed at week 3 and a marked LVH with interstitial fibrosis developed at week 19 in the irradiated hearts. In RIHD, cardiac miR-212 was overexpressed at week 3 and 19, and FOXO3 was repressed at the mRNA level only at week 19. By contrast, total FOXO3 protein level failed to decrease in response to heart irradiation at week 19. Other selected hypertrophy-associated target genes failed to change at the mRNA level in RIHD at week 19. Conclusions: LVH in RIHD was associated with cardiac overexpression of miR-212. However, miR-212 seems to play a role in the development of LVH via FOXO3-independent mechanisms in RIHD. As a central regulator of pathologic remodeling, miR-212 might become a novel target for RIHD-induced LVH and heart failure.